2019
DOI: 10.3390/molecules24071437
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Naphthoquinone Analogues: Potent Antibacterial Agents and Mode of Action Evaluation

Abstract: 1,4-Naphthoquinones have antibacterial activity and are a promising new class of compound that can be used to treat bacterial infections. The goal was to improve effective antibacterial agents; therefore, we synthesized a new class of naphthoquinone hybrids, which contain phenylamino-phenylthio moieties as significant counterparts. Compound 4 was modified as a substituted aryl amide moiety, which enhanced the antibacterial activity of earlier compounds 3 and 4. In this study, five bacterial strains Staphylococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 29 publications
4
77
0
Order By: Relevance
“…Among them, quinone moiety is one of the most important structures in drug discovery (Wellington, Kolesnikova, Nyoka, & McGaw, ). The studies of 1,4‐quinones have drawn a great deal of attention since their scaffold is an important pharmacophore (Jin, Ryu, Moon, Cho, & Yun, ; Lien, Huang, Teng, Wang, & Kuo, ; Ravichandiran, Masłyk et al, ; Ravichandiran, Sheet, Premnath, Kim, & Yoo, ) and amply found in numerous natural products. The first model from nature, prenylquinones, is an important class of compounds occurring in all living cells that contain characteristic 1,4‐quinone and isoprenyl moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, quinone moiety is one of the most important structures in drug discovery (Wellington, Kolesnikova, Nyoka, & McGaw, ). The studies of 1,4‐quinones have drawn a great deal of attention since their scaffold is an important pharmacophore (Jin, Ryu, Moon, Cho, & Yun, ; Lien, Huang, Teng, Wang, & Kuo, ; Ravichandiran, Masłyk et al, ; Ravichandiran, Sheet, Premnath, Kim, & Yoo, ) and amply found in numerous natural products. The first model from nature, prenylquinones, is an important class of compounds occurring in all living cells that contain characteristic 1,4‐quinone and isoprenyl moieties.…”
Section: Introductionmentioning
confidence: 99%
“…10) which contain phenylamino-phenylthio moieties as significant counterparts demonstrated major antibacterial activity against bacterial strains Staphylococcus aureus, Listeria monocytogenes, E. coli, P. aeruginosa, Salmonella bongori and Klebsiella pneumoniae. [57][58][59] Two naphthoquinone derivatives (38) and (39) (Fig. 10) had potential antimycobacterial activity against three Mycobacterium tuberculosis strains and did not exhibit cross-resistance with isoniazid and rifampicin; they could be promising scaffolds for the development of new therapeutic strategies against tuberculosis.…”
Section: Cardioprotective and Anti-ischemic Propertiesmentioning
confidence: 99%
“…Quinone, and mainly 1,4-naphthoquinone structures, are widely diffused in several structures of natural products and are often associated to a series of biological activities, including antibacterial [4], antifungal [5], antimalarial and anticancer properties, correlated to their high reactivity due to redox and acid/base behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid molecules involving norfloxacin [6,7] and quinones [4,[8][9][10][11] have been studied as antimicrobial agents but, to the best of our knowledge, no data have been reported so far on hybridization taking in account norfloxacin and naphtoquinone structures simultaneously. We report here on the synthesis of new hybrid norfloxacin-quinone derivatives, their in vitro antimicrobial activities and a computational analysis of the complexes with S. aureus DNA-gyrase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation